Pressure-Driven Batch Distillation Optimal Control for Ethanol-Water Separation - Stojkovic, Marija (Fine Chemical Engineering, 2023)
Ethanol-water separation by pressure-swing batch distillation in a double-batch rectifier system is a process under investigation. In this work, a complete global solution to the optimal control problem in the form of a sequential synthesis of controlled trajectories is derived. During this study, the optimal reflux strategy through cyclic operation was extended to the separation of a second non-ideal minimum boiling azeotrope of industrial importance. The optimal cyclic reflux ratio operating policy, brought significant reductions in time duration, going up to even 50%. Consequently even more significant reductions in energy expenditure, since the derived discontinuous energy function tends to show cyclic “behavior” as well. Lastly, the proposed strategy provides the possibility to highly recover the desired product even within a single period, and finally maybe even the most importantly, flexibility in operating different units within the time frame.